Academic and Non-Academic Profile Affecting the Nurse Licensure Examination Performance of the Nursing Graduates of a Higher Education Institution in Davao City - Pulgarinas Jr., Romeo (JPAIR Institutional Research, 2022)
The Nurse Licensure Examination is conducted by the Professional Regulatory Commission to screen Nursing graduates who will be licensed to practice nursing. The study aimed to determine the academic and non-academic profiles of the respondents and their possible correlation to the respondents’ Nurse Licensure Examination performance. Using total enumeration, sixty-seven Nursing graduates of the pioneering batch under CMO 14 s. 2009 were used as respondents. The academic profile included Nursing Care Management (NCM), Nurse Aptitude Test (NAT), English Proficiency, and Nursing Enhancement Program (NEP). The non-academic profile covered Emotional Quotient, the Otis-Lennon School Ability Test (OLSAT), and the Schedule of Examination. The study used the non-experimental descriptive-correlational research design. Frequency and percentage, mean, Pearson r, Chi-Square, and Linear Regression analysis were the statistical tools employed in the study. Results revealed that all individual parameters in the academic profile are significantly correlated to the licensure examination performance. On the other hand, only the OLSAT in the non-academic profile showed a significant correlation to the licensure examination performance. Finally, the regression model obtained in the study is written as NLEP = 18.139 + 0.413 (NCM) + 0.018 (NAT) – 0.195 (EngProf) + 0.399 (NEP).
Keywords: Education; academic and non-academic profile; nurse licensure examination performance; descriptive – correlation; linear regression analysis; Davao City